THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON CORPORATE SOCIAL RESPONSIBILITY - Ainun Soraya, Munawaroh; Kartika, Indri (LP2M IBK Nitro, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG) on Corporate Social Responsibility (CSR) disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The variables studied include board of commissioner activity, audit committee activity, environmental performance, and the number of directors. This study used quantitative methods with secondary data obtained from companies' annual reports. The research sample was selected using a purposive sampling technique, resulting in 59 companies with a total of 177 observations. Data analysis was performed using multiple linear regression with SPSS 25. The results show that Board of Commissioners activity has no effect on Corporate Social Responsibility (CSR) disclosure. Audit Committee activity has a significant positive effect on CSR. Environmental performance has a significant positive effect on CSR. The number of directors has no effect on CSR. These findings imply that the larger the company and the stronger its external oversight mechanisms, the higher the company's level of transparency in disclosing CSR information.